Female Unruliness in Slavonian Folk Playwriting and Folklore - Čale Feldman, Lada (Array, 1997)
The analysis presented in this paper has a double scope: it questions the role and the representative force of cultural and folklore intertexts in Slavonian folk playwriting, but focusing on a specific issue - on how these intertexts contribute to the construction of a diversity of female characters, often represented as "unruly" women, the only one responsible for conflicts in the possible worlds of analysed dramas.